Secondary battery binder, slurry, electrode, method for manufacturing a secondary battery, and secondary battery
Patent Information
- Application Number
- JP2025059669
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0007】 本開示の二次電池バインダーを含む二次電池は、充放電初期の電極の膨張収縮が好適に抑制される。
Smart Images

Figure 2026166615000001 
Figure 2026166615000002 
Figure 2026166615000003
Abstract
Description
[Technical Field]
[0001] This disclosure relates to a secondary battery binder, slurry, electrode, method for manufacturing a secondary battery, and a secondary battery. [Background technology]
[0002] In recent years, due to concerns about environmental impact, there has been growing interest in aqueous slurries using water as a dispersant, rather than slurries using organic solvents, and various binders for use in aqueous slurries are being investigated. For example, Patent Document 1 discloses the use of an aqueous slurry containing a latex-based binder. Furthermore, to increase the electrical capacity of secondary batteries, negative electrode active materials with high charge-discharge capacity, such as silicon, tin, or alloys containing these materials, are widely used. When using these negative electrode active materials with high charge-discharge capacity, a problem arises: expansion and contraction of the negative electrode active material due to the intercalation and release reactions of lithium ions during charging and discharging. Therefore, Patent Document 2 reports that using a specific copolymer is effective in suppressing expansion and contraction during charging and discharging. [Prior art documents] [Patent Documents]
[0003] [Patent Document 1] Japanese Patent Publication No. 2012-49061 [Patent Document 2] Special Publication No. 2020-533771 [Overview of the project] [Problems that the invention aims to solve]
[0004] However, even with the use of these specific copolymers, it was not sufficient to suppress the expansion of electrodes during charging and discharging of secondary batteries, especially in the initial stages of charging and discharging.
[0005] Accordingly, the present disclosure aims to provide a secondary battery binder that effectively suppresses electrode expansion during the initial stages of charging and discharging of secondary batteries. [Means for Solving the Problems]
[0006] The present disclosure includes the following aspects: [Item 1] A secondary battery binder comprising a copolymer containing a repeating unit represented by Formula (I) shown below and an acidic functional group-containing repeating unit, wherein in the copolymer, the content of the acidic functional group-containing repeating unit is 65 mol% or more, and in the copolymer, the amount of the acidic functional group-containing repeating unit per 1 mol of the repeating unit represented by Formula (I) is 30 mol or less. [Chemical Formula] [In the formula, R 1 is a hydrogen atom or a methyl group; m is independently an integer of 2 to 5, and n is independently an integer of 1 to 50 at each occurrence.] [Item 2] The secondary battery binder according to Item 1, wherein the copolymer further contains a nitrile group-containing repeating unit. [Item 3] The secondary battery binder according to Item 1 or 2, wherein in the copolymer, the amount of the acidic functional group-containing repeating unit per 1 mol of the repeating unit represented by Formula (I) is 5 to 30 mol. [Item 4] The secondary battery binder according to Item 2 or 3, wherein in the copolymer, the content of the nitrile group-containing repeating unit is 5 to 20 mol%. [Item 5] The secondary battery binder according to any one of Items 1 to 4, wherein in the copolymer, the content of the repeating unit represented by Formula (I) is 3 mol% or less. [Item 6] A slurry for secondary batteries, the slurry comprising the secondary battery binder according to any one of Claims 1 to 5, and water. [Item 7] The slurry according to Item 6, further comprising an electrode active material. [Item 8] A method for producing a secondary battery, comprising the step of applying the slurry according to claim 6 or 7. [Claim 9] An electrode comprising the secondary battery binder according to any one of claims 1 to 5, or a component derived from the secondary battery binder. [Claim 10] An electrode comprising a dried product of the slurry according to claim 6 or 7. [Claim 11] A secondary battery comprising the electrode according to claim 9 or 10. [Effect of the Invention]
[0007] In the secondary battery comprising the secondary battery binder of the present disclosure, expansion and contraction of the electrode at the initial stage of charge and discharge are suitably suppressed. [Mode for Carrying Out the Invention]
[0008] <Definitions of Terms, etc.> In the present specification, regardless of whether "each independently" or a similar expression is explicitly stated, unless otherwise stated as an exception, when a term (symbol) that may appear a plurality of times in a chemical structure is defined, the definition is applied independently to each occurrence.
[0009] In the present specification, "(meth)acryl" means "acryl or methacryl", and "(meth)allyl" means "allyl or methallyl".
[0010] In the present specification, when a plurality of lower limit values and a plurality of upper limit values are described separately, any lower limit value and upper limit value may be selected, and a numerical range in the combination range of the selected lower limit value and upper limit value may be selected.
[0011] <Secondary Battery Binder> The secondary battery binder in the present disclosure is used for enhancing the binding property between particles inside the electrode and the binding property between the active material layer and the current collector in a secondary battery, and for enhancing the binding property between inorganic particles in the separator layer and the binding property with the base material layer, and the like.
[0012] The secondary battery binder in this disclosure is A secondary battery binder comprising a copolymer containing repeating units represented by the following formula (I) and repeating units containing acidic functional groups, In the copolymer, the amount of the acidic functional group-containing repeating unit is 65 mol% or more. The copolymer is a secondary battery binder in which the amount of the acidic functional group-containing repeating unit per mole of the repeating unit represented by formula (I) is 30 moles or less. [ka] [In the formula, R 1 [where m is a hydrogen atom or a methyl group; m is an integer between 2 and 5 independently, and n is an integer between 1 and 50 independently in each occurrence.]
[0013] [Copolymer] The secondary battery binder in this disclosure contains a copolymer.
[0014] (The repeating unit represented by formula (I)) The copolymer contains repeating units represented by formula (I).
[0015] R 1 Preferably, it is a hydrogen atom.
[0016] m is independently between 2 and 5, preferably 2 or 3, more preferably 2.
[0017] n may be 1 or more, 2 or more, 3 or more, 5 or more, 6 or more, 7 or more, or 10 or more, and may also be 15 or less, 10 or less, 6 or less, 5 or less, 3 or less, or 2 or less, preferably 5 or less, more preferably 3 or less, and particularly preferably 1.
[0018] Examples of repeating units represented by formula (I) include those derived from 2-hydroxyethyl (meth)acrylate (m=2, n=1) and polyethylene glycol mono(meth)acrylate (m=2, n≧2). These repeating units represented by formula (I) may be used individually or in combination of two or more types. Specifically, the factors that lead to the repeating unit represented by equation (I) are: Brembo AE-200, Brembo AE-400, Brembo E, Brembo PE-90, Brembo PE-200, Brembo PE-350, Brembo P, Brembo PP-1000, Brembo PP-500, Brembo PP-800, Brembo AP-400, Brembo 50PEP-300, Brembo 55PET-800, Brembo 10PPB-500B, all manufactured by NOF Corporation. Polyethylene Glycol Monomethacrylate manufactured by Tokyo Chemical Industry Co., Ltd. PEGMA200, PEGMA400, and PEGMA440 manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. Examples include Sigma-Aldrich's Poly(ethylene glycol) methacrylate, average Mn360 and Poly(ethylene glycol) methacrylate, average Mn500.
[0019] (Repeating unit containing acidic functional group) The copolymers in this disclosure include repeating units containing acidic functional groups. The acidic functional groups may be anionic groups such as carboxyl groups, sulfonic acid groups, phosphoric acid groups, and nitrate groups, for example, carboxyl groups or sulfonic acid groups, and particularly carboxyl groups. Examples of repeating units having acidic functional groups include repeating units derived from (meth)acrylic acid, maleic acid, vinyl sulfonic acid, or (meth)allyl sulfonic acid, with repeating units derived from (meth)acrylic acid being preferred. These acidic functional group-containing repeating units may exist individually or in combination of two or more types. Furthermore, these groups may exist in the form of salts, and an example of a countercation in that case is a metal ion used in the basic compounds described later.
[0020] [Other structures of copolymers, etc.] Copolymers are obtained by polymerizing one or more monomers. Copolymers may be vinyl polymers. Vinyl polymers are polymers obtained by polymerizing vinyl monomers. Here, vinyl monomers may be compounds having polymerizable carbon-carbon double bonds (ethylenically unsaturated double bonds) (>C=C<), and may be monomers containing vinyl groups, vinylene groups, vinylidene groups, acryloyl groups, methacryloyl groups, or derivative groups thereof. Copolymers may be (meth)acrylic copolymers that contain repeating units derived from monomers having acryloyl groups or methacryloyl groups.
[0021] The copolymers in this disclosure are preferably water-soluble polymers that are dispersible in water on their own and are particularly water-soluble. In this disclosure, a copolymer is considered "water-soluble" if the insoluble content when 2.0 g of the copolymer is dissolved in 100 g of water at 25°C is 20% by mass or less relative to the copolymer. The insoluble content when 2.0 g of the copolymer is dissolved in 100 g of water at 25°C is preferably 5% by mass or less, more preferably 1% by mass or less.
[0022] The copolymer may be a random polymer or a block polymer, for example, a random polymer.
[0023] (Non-hydrophilic repeating unit) The copolymer may have non-hydrophilic repeating units. Non-hydrophilic repeating units do not have hydrophilic groups (e.g., ionic groups). Examples of non-hydrophilic repeating units include repeating units derived from alkyl (meth)acrylates or vinyl chloride, or repeating units derived from nitrile group-containing monomers. These non-hydrophilic repeating units may be present individually or in combination of two or more types.
[0024] (Repeating unit containing nitrile group) The copolymer of the present disclosure preferably further comprises nitrile group-containing repeating units.
[0025] As an example of a suitable repeating unit containing a nitrile group, formula: -[CH2-C(R 5 )(C≡N)]- [In the formula, R 5 This is a hydrogen atom or CH3. A repeating unit (3) represented by is an example.
[0026] In the repeating unit (3), R 5 Preferably, it is a hydrogen atom.
[0027] The nitrile group-containing repeating unit is preferably a repeating unit derived from (meth)acrylonitrile.
[0028] (Hydrophilic repeating unit) The copolymer may further have hydrophilic repeating units other than the repeating unit represented by formula (I) and the repeating unit containing an acidic functional group. The hydrophilic repeating unit contains a hydrophilic group. Examples of hydrophilic groups include anionic groups such as carboxyl groups, sulfonic acid groups, phosphoric acid groups, and nitrate groups; cationic groups such as amino groups; hydroxyl groups; polyoxyethylene groups (e.g., with 2 or more, 5 or more, or 10 or more repeating units); and nonionic hydrophilic groups such as amide groups. The anionic and cationic groups may be in the form of free acid / base, or some or all of them may be in the form of a salt.
[0029] The copolymers in this disclosure may have nonionic hydrophilic repeating units. Examples of nonionic hydrophilic repeating units include repeating units derived from (meth)acrylamide, hydroxyalkyl (meth)acrylate, hydroxyalkyl (meth)acrylamide, polyoxyalkylene (meth)acrylate, polyoxyalkylene (meth)acrylamide, vinyl alcohol, etc.
[0030] [Properties of copolymers, etc.] The properties of the copolymer are shown below.
[0031] (molecular weight, etc.) The Mw (weight-average molecular weight) of the copolymer according to GPC-RI may be 10,000 or more, 50,000 or more, 100,000 or more, 300,000 or more, 500,000 or more, 700,000 or more, or 1,500,000 or more, preferably 100,000 or more, more preferably 300,000 or more, and may also be 3,000,000 or less, 2,000,000 or less, 1,000,000 or less, 800,000 or less, or 500,000 or less, preferably 3,000,000 or less, more preferably 2,000,000 or less.
[0032] The Mw / Mn (breadth of molecular weight distribution) of the copolymer as determined by GPC-RI may be 4.0 or higher, 5.0 or higher, 7.5 or higher, 10 or higher, or 12.5 or higher, preferably 4.0 or higher, more preferably 7.5 or higher, and may also be 25 or lower, 20 or lower, 15 or lower, 10 or lower, 7.5 or lower, or 5 or lower, preferably 25 or lower, more preferably 15 or lower.
[0033] [Composition of copolymer, etc.] If the copolymer according to this disclosure is manufactured using multiple monomers that are contained within a single repeating unit species, the total amount of the multiple monomers shall be defined as the amount of the repeating unit species. For example, if the copolymer has both 2-hydroxyethyl acrylate and polyethylene glycol monoacrylate as repeating unit species represented by formula (I), the total amount of both shall be defined as the "amount of the repeating unit represented by formula (I)".
[0034] In the copolymer, the amount of repeating units represented by formula (I) may be 0.1 mol% or more, 0.5 mol% or more, 1 mol% or more, 2 mol% or more, 3 mol% or more, 5 mol% or more, or 10 mol% or more, preferably 1 mol% or more, more preferably 2 mol% or more. In the copolymer, the amount of repeating units represented by formula (I) may be 30 mol% or less, 20 mol% or less, 10 mol% or less, 7 mol% or less, 5 mol% or less, or 3 mol% or less, preferably 15 mol% or less, more preferably 3 mol% or less. If the amount of repeating units represented by formula (I) is above the lower limit and below the upper limit, the secondary battery binder of this disclosure may have suitable toughness when used as an electrode.
[0035] In the copolymer, the amount of repeating units containing acidic functional groups is 65 mol% or more, and may be 70 mol% or more, 75 mol% or more, 80 mol% or more, 85 mol% or more, or 90 mol% or more, preferably 65 mol% or more, more preferably 70 mol% or more. In the copolymer, the amount of repeating units containing acidic functional groups may be 95 mol% or less, 90 mol% or less, 85 mol% or less, or 80 mol% or less, preferably 95 mol% or less, more preferably 90 mol% or less. If the amount of repeating units containing acidic functional groups is above the lower limit, the electrode containing the secondary battery binder of this disclosure may have suitable hardness. If the amount of repeating units containing acidic functional groups is below the upper limit, embrittlement of the electrode containing the secondary battery binder of this disclosure can be suppressed.
[0036] In the copolymer, the amount of acidic functional group-containing repeating units per mole of repeating units represented by formula (I) is 2 moles or more, and may be, for example, 3 moles or more, 4 moles or more, 7 moles or more, 10 moles or more, 15 moles or more, or 20 moles or more, preferably 5 moles or more, more preferably 10 moles or more. In the copolymer, the amount of acidic functional group-containing repeating units per mole of repeating units represented by formula (I) is 30 moles or less, and may be, for example, 28 moles or less, 27 moles or less, 25 moles or less, 20 moles or less, 15 moles or less, 10 moles or less, or 8 moles or less, preferably 30 moles or less, more preferably 27 moles or less.
[0037] In the copolymer, the amount of hydrophilic repeating units other than the repeating units represented by formula (I) and the repeating units containing acidic functional groups may be 0 mol% or more, 0.1 mol% or more, 0.5 mol% or more, 1 mol% or more, 3 mol% or more, 5 mol% or more, 10 mol% or more, 15 mol% or more, or 20 mol% or more. In the copolymer, the amount of hydrophilic repeating units other than the repeating units represented by formula (I) and the repeating units containing acidic functional groups may be 35 mol% or less, 25 mol% or less, 15 mol% or less, 10 mol% or less, 5 mol% or less, 3 mol% or less, 1 mol% or less, or 0.1 mol% or less, preferably 5 mol% or less.
[0038] In the copolymer, the amount of nitrile group-containing repeating units may be 0 mol% or more, 1 mol% or more, 3 mol% or more, 5 mol% or more, 7 mol% or more, 10 mol% or more, 12 mol% or more, 15 mol% or more, or 20 mol% or more, preferably 5 mol% or more, more preferably 12 mol% or more. In the copolymer, the amount of nitrile group-containing repeating units may be 30 mol% or less, 25 mol% or less, 20 mol% or less, 15 mol% or less, 10 mol% or less, or 5 mol% or less, preferably 30 mol% or less, more preferably 20 mol% or less. If the amount of nitrile group-containing repeating units is above the above lower limit, the secondary battery binder of this disclosure has suitable chemical and physical durability, and the electrode containing the secondary battery binder can have its degradation due to repeated charging and discharging suppressed.
[0039] In the copolymer, the amount of nitrile group-containing repeating units per mole of repeating units represented by formula (I) may be 0 moles or more, 0.05 moles or more, 0.1 moles or more, 0.3 moles or more, 0.5 moles or more, 1.0 moles or more, 1.2 moles or more, 1.5 moles or more, 2.0 moles or more, 3.0 moles or more, 4.0 moles or more, or 5.0 moles or more, preferably 0.5 moles or more, more preferably 1.0 mole or more. In the copolymer, the amount of nitrile group-containing repeating units per mole of repeating units represented by formula (I) may be 30 moles or less, 25 moles or less, 20 moles or less, 15 moles or less, 10 moles or less, 8 moles or less, or 5 moles or less, preferably 8 moles or less, more preferably 5 moles or less.
[0040] The composition ratio of each repeating unit in the copolymer according to this disclosure may be substantially the same as the blending ratio of monomers used in the production of the copolymer. Furthermore, the composition of each repeating unit in the copolymer is 1 HNMR and 13 It can be measured by CNMR.
[0041] [Method for producing copolymers] The method for producing the copolymer is not particularly limited and can be produced using known copolymer production methods. Preferably, it can be synthesized by aqueous radical polymerization. Specifically, a radical polymerization initiator and, if necessary, a chain transfer agent can be added to the monomer mixture, and the polymerization reaction can be carried out at a reaction temperature of about 50 to 100°C (e.g., 60 to 70°C) while stirring. The reaction time is not particularly limited and may be about 1 to 10 hours. After the reaction time has elapsed, the copolymer may be further aged at a temperature of reaction temperature +3°C to +10°C (e.g., +4°C to +8°C) for 15 minutes to 2 hours (e.g., 30 minutes to 1.5 hours). Aging can reduce the amount of unreacted monomers.
[0042] The monomer concentration at the start of polymerization may be 5% by mass or more, 10% by mass or more, 15% by mass or more, 20% by mass or more, or 25% by mass or more, and may also be 30% by mass or less, 25% by mass or less, 20% by mass or less, 15% by mass or less, or 10% by mass or less, and in one embodiment, it may be 10% by mass or more and 11% by mass or less, 15% by mass or more and 17% by mass or less, or 11% by mass or more and 13% by mass or less.
[0043] Various known initiators can be used without particular limitation. Examples of radical polymerization initiators include persulfates such as potassium persulfate and ammonium persulfate; redox polymerization initiators combining the persulfate with a reducing agent such as sodium bisulfite; and azo initiators such as 2,2'-azobis-2-amidinopropane dihydrochloride (NC-32) (V-50) and 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride (VA-044). The amount of radical polymerization initiator used is preferably about 0.05 to 2% by mass, and more preferably about 0.1 to 1.0% by mass, based on 100% by mass of the monomer group that serves as the raw material for the copolymer in this disclosure.
[0044] Each polymerization condition can be appropriately set according to the structure of the target compound.
[0045] [Quantity of copolymer] The amount of copolymer may be 25% by mass or more, 50% by mass or more, 75% by mass or more, 95% by mass or more, or 99% by mass or more in the secondary battery binder, preferably 50% by mass or more, more preferably 75% by mass or more, and may also be 99% by mass or less, 90% by mass or less, 80% by mass or less, or 70% by mass or less.
[0046] [Basic compounds] The secondary battery binder of this disclosure may contain a basic compound. The basic compound is preferably a compound capable of neutralizing acidic functional groups in the copolymer. Examples of such basic compounds include alkali metal hydroxides such as sodium hydroxide, lithium hydroxide, and potassium hydroxide; alkali metal carbonates such as lithium carbonate, sodium carbonate, and potassium carbonate; alkaline earth metal hydroxides such as calcium hydroxide, barium hydroxide, and magnesium hydroxide; and amine compounds such as trimethylamine, triethylamine, and tri-n-butylamine. From the viewpoint of imparting appropriate viscosity to the secondary battery binder, alkali metal hydroxides are preferred, and sodium hydroxide is preferred.
[0047] The amount of the basic compound in the secondary battery binder may be 10% by mass or more, 20% by mass or more, 25% by mass or more, 30% by mass or more, or 35% by mass or more, preferably 20% by mass or more, more preferably 25% by mass or more, and may also be 40% by mass or less, 35% by mass or less, or 25% by mass or less, preferably 40% by mass or less, more preferably 35% by mass or less.
[0048] The basic compound may exist in the secondary battery binder or in the slurry containing the secondary battery binder in the form of the basic compound as is, in the form of a free ion, or in a form associated with a functional group (e.g., an acidic functional group) in the copolymer, or in a form ionically bonded to it.
[0049] [Crosslinking agent] The secondary battery binder in this disclosure may optionally contain a crosslinking agent. Any crosslinking agent that can be used as a crosslinking agent in the polymerization of (meth)acrylic monomers may be used, for example isocyanate crosslinking agents, epoxy crosslinking agents, vinyl crosslinking agents, melamine crosslinking agents, peroxide crosslinking agents, as well as urea crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, carbodiimide crosslinking agents, oxazoline crosslinking agents, aziridine crosslinking agents, amine crosslinking agents, etc. Among these, isocyanate crosslinking agents, epoxy crosslinking agents, or vinyl crosslinking agents are preferred.
[0050] Specific examples of isocyanate-based crosslinking agents include, for example, methylene diisocyanate, toluene diisocyanate, butylene diisocyanate, hexamethylene diisocyanate, diphenylmethane diisocyanate, cyclohexylene diisocyanate, xylylene diisocyanate, and isocyanurate derivatives of examethylene diisocyanate.
[0051] Specific examples of epoxy crosslinking agents include N,N,N',N'-tetraglycidyl-m-xylenediamine, diglycidylaniline, 1,3-bis(N,N-glycidylaminomethyl)cyclohexane, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, diglycidyl adipate ester, diglycidyl o-phthalate ester, and the like.
[0052] Examples of vinyl crosslinking agents include divinylbenzene, N,N'-methylenebis(acrylamide), divinyl ether, bis(vinylsulfonyl)methane, 1,10-bis(acryloyloxy)decane, divinyl adipate, 1,4-bis[(vinyloxy)methyl]cyclohexane, diethylene glycol divinyl ether, diethylene glycol diacrylate, 1,4-cyclohexanedicarboxylate diallyl, allyl ether, 3,9-divinyl-2,4,8,10-tetraoxaspiro[5.5]undecane, and the like.
[0053] The amount of crosslinking agent in the binder may be 0% by mass or more, 0.001% by mass or more, 0.005% by mass or more, 0.01% by mass or more, 0.03% by mass or more, 0.05% by mass or more, 0.07% by mass or more, 0.1% by mass or more, 0.2% by mass or more, or 0.5% by mass or more, and may also be 5% by mass or less, 3% by mass or less, 2% by mass or less, 1% by mass or less, or 0.8% by mass or less, for example, 0.1% by mass.
[0054] [Other binder ingredients] The secondary battery binder in this disclosure may contain other binder components in addition to copolymers and basic compounds. Examples of other binder components include known binder resins, such as styrene-butadiene rubber (SBR), styrene-ethylene-butylene-styrene copolymer (SEBS), polyimide (PI), polyamide, and ethylene vinyl acetate copolymer (EVA).
[0055] The amount of other binder components may be 0% by mass or more, 0.5% by mass or more, 5% by mass or more, 10% by mass or more, or 25% by mass or more in the binder, and may also be 50% by mass or less, 40% by mass or less, 30% by mass or less, 20% by mass or less, 10% by mass or less, or 5% by mass or less, for example, 3% by mass or less.
[0056] <Slurry> The slurry of this disclosure comprises the aforementioned secondary battery binder and water, and may further contain an electrode active material. The slurry may also contain battery particles such as conductive additives and other liquid media, and is typically an electrode slurry containing an electrode active material. The slurry may be a positive electrode slurry containing a positive electrode active material or a negative electrode slurry containing a negative electrode active material.
[0057] [Liquid media] The slurry contains a liquid medium (aqueous medium) containing water. The liquid medium is preferably water alone from the viewpoint of environmental impact concerns, but may also contain an organic solvent, such as alcohol (ethanol, methanol, isopropyl alcohol, etc.). The amount of organic solvent may be 30% by mass or less, 10% by mass or less, 5% by mass or less, or 3% by mass or less in the liquid medium, and is preferably 10% by mass or less.
[0058] [Amount of liquid medium] The amount of liquid medium is prepared to match the desired slurry solid content concentration. The amount of liquid medium may be 20 parts by mass or more, 60 parts by mass or more, 80 parts by mass or more, or 100 parts by mass or more, preferably 30 parts by mass or more, and may also be 200 parts by mass or less, 100 parts by mass or less, or 40 parts by mass or less, preferably 160 parts by mass or less, more preferably 150 parts by mass or less.
[0059] [Secondary Battery Binder] The slurry contains a secondary battery binder. The types of secondary battery binders are as described above.
[0060] [Amount of rechargeable battery binder] The amount of secondary battery binder may be 0.1% by mass or more, 0.3% by mass or more, 0.5% by mass or more, 1.0% by mass or more, 1.5% by mass or more, 3.0% by mass or more, or 5.0% by mass or more, of the slurry solid content (total amount of binder, active material, and conductive additive), preferably 0.3% by mass or more, and may also be 10% by mass or less, 7.5% by mass or less, 5.0% by mass or less, 3.0% by mass or less, 1.0% by mass or less, or 0.5% by mass or less, preferably 3.0% by mass or less, more preferably 1.0% by mass or less. An amount above the lower limit is preferable from the viewpoint of achieving good binder effects. An amount below the upper limit is preferable from the viewpoint of achieving high battery capacity.
[0061] [Active material] The active material is an electrode active material, and examples include a negative electrode active material or a positive electrode active material. For example, if the active material is a negative electrode active material, it may include, for example, a carbon material, and may also include, for example, at least one of silicon and silicon oxide. Specific materials for the negative electrode active material and the positive electrode active material are exemplified below.
[0062] (Negative electrode active material) The negative electrode active material is not particularly limited, and any negative electrode active material used in the art may be used.
[0063] As the negative electrode active material, carbon materials such as crystalline carbon or amorphous carbon may be used. Examples of crystalline carbon include graphite, such as natural or artificial graphite, which may be amorphous, plate-like, flake-like, spherical, or fibrous. Examples of amorphous carbon include soft carbon (easily graphitizable carbon) or hard carbon (difficult to graphitize carbon), mesophase pitch carbide, and calcined coke.
[0064] As the negative electrode active material, a material capable of occluding and releasing a large amount of lithium ions, such as silicon (Si), tin (Sn), or Ti (titanium), may be used. These materials can be used in the form of a simple substance, an alloy, a compound, a solid solution, or a composite active material including a silicon-containing material, a tin-containing material, and a titanium-containing material. Examples of the silicon-containing material include Si, Si / C, SiOx (0.05<x<1.95), or an alloy, compound, or solid solution in which a part of Si is substituted with at least one element selected from the group consisting of B, Mg, Ni, Ti, Mo, Co, Ca, Cr, Cu, Fe, Mn, Nb, Ta, V, W, Zn, C, N, and Sn. The silicon-containing material may be a silicon oxide. Examples of the tin-containing material include Ni₂Sn₄, Mg₂Sn, SnOx (0<x<2), SnO₂, SnSiO₃, and LiSnO. Examples of the titanium-containing material include Li₂TiO₃, Li₄Ti₅O 12 and the like, such as lithium titanate, and titanium-niobium composite compounds. One of these materials may be used alone, or two or more thereof may be used in combination. Among these, silicon or silicon oxide is preferable, and for example, elemental silicon or silicon oxide may be used.
[0065] As the negative electrode active material, it is more preferable to use, as the negative electrode active material, a composite obtained by mixing a first negative electrode active material which is silicon or silicon oxide and a second negative electrode active material which is a carbon material. As the carbon material, any carbon material commonly used in secondary batteries, particularly non-aqueous electrolyte secondary batteries, can be used, and crystalline carbon, amorphous carbon, or a combination thereof may be used. Examples of the crystalline carbon include those described above.
[0066] The method for producing the negative electrode active material is not particularly limited. When producing an active material composite in which the first negative electrode active material and the second negative electrode active material are mixed, a method in which both are uniformly dispersed may be adopted, and for example, a method of mixing the first negative electrode active material and the second negative electrode active material with a ball mill may be mentioned.
[0067] (Positive Electrode Active Material) The positive electrode active material is not particularly limited, and any positive electrode active material used in the technical field of the present invention may be used.
[0068] The positive electrode active material may be a lithium-containing composite oxide. Examples of the lithium-containing composite oxide include LiMnO2, LiFeO2, LiCoO2, LiMn2O4, Li2FeSiO4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi x Co y M z O2 (provided that 0≦x<1, 0≦y<1, 0≦z<1, x+y+z=1, and M is at least one element selected from the group consisting of Mn, V, Mg, Mo, Nb, Fe, Cu and Al), LiMn (1-w) Fe w PO4 (provided that 0<w<1), LiFePO4, and the like.
[0069] [Amount of Active Material] The amount of the active material in the solid content of the slurry (the total amount of the binder, the active material and the conductive aid) may be 35 mass% or more, 55 mass% or more, 75 mass% or more, or 95 mass% or more, preferably 55 mass% or more, more preferably 75 mass% or more, and may be 95 mass% or less, 90 mass% or less, or 85 mass% or less.
[0070] [Conductive Aid] As a conductive additive, conductive additives used in this art can be used. The conductive additive is not particularly limited as long as it is conductive, but carbon powder is preferred. Examples of commonly used carbon powders include acetylene black (AB), Ketjenblack (KB), graphite, carbon fiber, carbon tubes, graphene, amorphous carbon, hard carbon, soft carbon, glassy carbon, carbon nanofiber, and carbon nanotubes. These may be used individually or in combination of two or more.
[0071] [Amount of conductive additive] The amount of conductive additive may be 0.1% by mass or more, 1.0% by mass or more, or 5.0% by mass or more, preferably 0.3% by mass or more, and may also be 10% by mass or less, 5.0% by mass or less, or 1.0% by mass or less, preferably 3.0% by mass or less, more preferably 1.0% by mass or less.
[0072] [Dispersing agent] The slurry of this disclosure may further contain a dispersion aid. Preferred dispersion aids are organic acids containing at least one substituent selected from the group consisting of a hydroxyl group, an amino group, and an imino group, and a carboxyl group, or humic acid. Examples of organic acids having a hydroxyl group and a carboxyl group include lactic acid, tartaric acid, citric acid, malic acid, glycolic acid, tartonic acid, glucuronic acid, and humic acid. Examples of organic acids having an amino group and a carboxyl group include glycine, alanine, phenylalanine, 4-aminobutyric acid, leucine, isoleucine, lysine, glutamic acid, aspartic acid, glutamine, asparagine, histidine, tryptophan, cysteine, and polymers thereof. Examples of organic acids having an imino group and a carboxyl group include proline, 3-hydroxyproline, 4-hydroxyproline, and pipecolic acid. Among these, glucuronic acid, humic acid, glycine, polyglycine, aspartic acid, or glutamic acid are preferred from the standpoint of ease of availability.
[0073] [Amount of dispersing agent] The amount of the dispersing agent may be 0.1% by mass or more, 1.0% by mass or more, or 3.0% by mass or more, preferably 0.3% by mass or more, and may also be 5.0% by mass or less, 3.0% by mass or less, or 1.0% by mass or less, preferably 3.0% by mass or less, more preferably 1.0% by mass or less.
[0074] [Other ingredients] The slurry of this disclosure may contain other components, such as conventional additives.
[0075] [Amount of other ingredients] The amount of other components (each or total) may be 0.1% by mass or more, 1.0% by mass or more, 3.0% by mass or more, or 5.0% by mass or more, preferably 0.3% by mass or more, and may also be 10% by mass or less, 5.0% by mass or less, 1.0% by mass or less, or 0.5% by mass or less, preferably 3.0% by mass or less, more preferably 1.0% by mass or less.
[0076] [Method for manufacturing slurry] The slurry manufacturing method of the present disclosure is manufactured by mixing components. For example, in the case of electrodes, a binder, a liquid medium, an active material, and optionally a conductive additive, a dispersion additive, etc., are mixed to form a slurry. The timing of adding the liquid medium is not particularly limited; the secondary battery binder of the present disclosure may be dispersed or dissolved in the liquid medium beforehand, and then the active material, etc., may be mixed in a solid state, and then the liquid medium may be added to form a paste-like slurry.
[0077] <Electrode> The electrodes of this disclosure are electrodes for secondary batteries and include the secondary battery binder (or components derived from the secondary battery binder) and active material as described above in this disclosure. That is, the electrodes of this disclosure can be manufactured, for example, by coating the slurry of this disclosure onto a current collector and drying it. Therefore, the electrodes may include the dried slurry. In this disclosure, "components derived from the secondary battery binder" means components produced when a part of the binder decomposes or reacts due to heating, drying, solvent immersion, etc.
[0078] The slurry may be dried at room temperature (e.g., 25°C). Room temperature drying may be carried out under reduced pressure (e.g., 0.05 MPa or less, 0.01 MPa or less). The time for room temperature drying may be, for example, 6 hours or more, and may be 72 hours or less, 48 hours or less, 24 hours or less, or 18 hours or less, preferably 48 hours or less.
[0079] Drying of the slurry is preferably carried out by heat drying. The temperature during heat drying may be 70°C or higher, 110°C or higher, or 130°C or higher, preferably 70°C or higher, and also 250°C or lower, 150°C or lower, or 125°C or lower, preferably 150°C or lower. Heat drying may be carried out under reduced pressure (for example, 0.05 MPa or lower, 0.01 MPa or lower). The time for heat drying may be 1 hour or more, 6 hours or more, or 15 hours or more, preferably 6 hours or more, and also 72 hours or less, 48 hours or less, 24 hours or less, or 18 hours or less, preferably 24 hours or less.
[0080] When the electrode of this disclosure is the negative electrode, the material constituting the current collector may be, for example, a conductive substance such as C, Cu, Ni, Fe, V, Nb, Ti, Cr, Mo, Ru, Rh, Ta, W, Os, Ir, Pt, Au, Al, or an alloy containing two or more of these conductive substances (for example, stainless steel). The current collector may also be Fe plated with Cu. From the viewpoint of high electrical conductivity, excellent stability in the electrolyte, and oxidation resistance, Cu, Ni, stainless steel, etc. are preferred as the material for the current collector of the negative electrode, and Cu or Ni are even more preferred from the viewpoint of material cost.
[0081] When the electrode of this disclosure is the positive electrode, the material constituting the current collector may be, for example, a conductive substance such as C, Ti, Cr, Mo, Ru, Rh, Ta, W, Os, Ir, Pt, Au, Al, or an alloy containing two or more of these conductive substances (for example, stainless steel). From the viewpoint of high electrical conductivity, stability in the electrolyte, and excellent oxidation resistance, C, Al, stainless steel, etc. are preferred as the material for the current collector of the positive electrode, and Al is further preferred from the viewpoint of material cost.
[0082] The shape of the current collector is not particularly limited; for example, foil-shaped substrates, three-dimensional substrates, etc., can be used. Furthermore, using a three-dimensional substrate (foamed metal, mesh, woven fabric, nonwoven fabric, expanded material, etc.) tends to result in good high-rate charge and discharge characteristics.
[0083] <Battery> The secondary battery of this disclosure includes the secondary battery electrodes of this disclosure as described above. The secondary battery of this disclosure may be any secondary battery of this disclosure that comprises the secondary battery electrodes of this disclosure as either the positive electrode or the negative electrode, or both. The secondary battery of this disclosure is manufactured using the secondary battery electrodes of this disclosure (i.e., using the secondary battery binder of this disclosure) by a method used in the art.
[0084] The secondary battery of this disclosure is preferably a non-aqueous electrolyte secondary battery, and more preferably a lithium-ion secondary battery. Since lithium-ion secondary batteries need to contain lithium ions, lithium salts are preferred as the electrolyte. Examples of lithium salts include lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, and lithium trifluoromethanesulfonate imide. The electrolyte can be used alone or in combination of two or more types.
[0085] Examples of electrolytes that can be used include propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, and γ-butyrolactone. The electrolyte can be used individually or in combination of two or more. In particular, propylene carbonate alone, a mixture of ethylene carbonate and diethyl carbonate, or γ-butyrolactone alone are preferred. The mixing ratio of the above-mentioned mixture of ethylene carbonate and diethyl carbonate can be arbitrarily adjusted within the range where one component accounts for 10 to 90% by volume.
[0086] For other secondary battery configurations, known secondary battery configurations can also be adopted.
[0087] Although embodiments have been described above, it should be understood that various modifications to the form and details are possible without departing from the spirit and scope of the claims. [Examples]
[0088] The present disclosure will be described in detail below with reference to examples, but the present disclosure is not limited to these examples.
[0089] The meanings of the abbreviations are as follows: AN: Acrylonitrile AA: Acrylic acid 2-HEA: 2-hydroxyethyl acrylate (m=2, n=1 in formula (I)) AE-200: Bremmer AE-200 manufactured by NOF Corporation, terminal hydroxyl group polyethylene glycol monoacrylate (formula (I) in which R 1 (=H, m=2, n≈4.5) 2-MEA: 2-methoxyethyl acrylate HAAm: N-(hydroxymethyl)acrylamide MBAA: N,N'-methylenebis(acrylamide) DEGDA: Diethylene glycol diacrylate
[0090] <Preparation of copolymer> The copolymer was prepared according to the procedure described below.
[0091] [Example 1] A monomer aqueous solution was prepared by adding 29.5 g (0.41 mol) of acrylic acid (AA), 34.2 g (0.41 mol) of 48% by mass sodium hydroxide aqueous solution, 4.0 g (0.08 mol) of acrylonitrile (AN), 1.7 g (0.01 mol) of 2-hydroxyethyl acrylate (2-HEA), 0.27 g of potassium persulfate, and 50 g of deionized water to a 500 mL vial that could be sealed, and mixing the mixture. Separately from the above, 182.2 g of deionized water was charged into a 1 L reaction vessel equipped with a stirrer, thermometer, N2 gas inlet tube, reflux condenser, and dropping funnel. After deoxygenating the system by blowing in N2 gas, the internal temperature was raised to 70°C. Subsequently, the prepared monomer aqueous solution was added to the reaction vessel dropwise over 3 hours using a dropping funnel while stirring. After addition, the internal temperature was maintained at 70°C for 2 hours. After that, the internal temperature was cooled to below 40°C to obtain an aqueous solution containing the copolymer.
[0092] [Example 2] In a 1 L reaction vessel equipped with a stirrer, thermometer, N2 gas inlet tube, reflux condenser, and dropping funnel, 317.8 g of deionized water was charged, and N2 gas was blown in to deoxygenate the system. Then, 23.4 g (0.32 mol) of AA, 27.0 g (0.32 mol) of 48% by mass sodium hydroxide aqueous solution, 1.3 g (0.02 mol) of AN, 17.4 g (0.15 mol) of 2-HEA, 0.08 g (0.0005 mol) of MBAA, and 1.22 g of potassium persulfate were charged, and the internal temperature was raised to 70°C and maintained for 5 hours. After that, the internal temperature was cooled to below 40°C to obtain an aqueous solution containing the copolymer.
[0093] [Example 3] A monomer aqueous solution was prepared by mixing 35.5 g (0.49 mol) of AA, 41.0 g (0.49 mol) of 48% by mass sodium hydroxide aqueous solution, 4.8 g (0.09 mol) of AN, 2.1 g (0.02 mol) of 2-HEA, 0.32 g of potassium persulfate, 0.93 g (0.006 mol) of MBAA, and 218.1 g of deionized water in a resealable vial with an internal volume of 500 mL. Separately from the above, 182.2 g of deionized water was charged into a 1 L reaction vessel equipped with a stirrer, thermometer, N2 gas inlet tube, reflux condenser, and dropping funnel. After deoxygenating the system by blowing in N2 gas, the internal temperature was raised to 70°C. Subsequently, the prepared monomer aqueous solution was added to the reaction vessel dropwise over 3 hours using a dropping funnel while stirring. After addition, the internal temperature was maintained at 70°C for 2 hours. After that, the internal temperature was cooled to below 40°C to obtain an aqueous solution containing the copolymer.
[0094] [Example 4] An aqueous solution containing the copolymer was obtained in the same manner as in Example 1, except that 30.3 g (0.42 mol) of AA, 35.0 g (0.42 mol) of 48% by mass sodium hydroxide aqueous solution, 4.8 g (0.09 mol) of AN, 10.5 g (0.09 mol) of 2-HEA, 0.32 g of potassium persulfate, and 221.9 g of deionized water were used.
[0095] [Example 5] An aqueous solution containing the copolymer was obtained in the same manner as in Example 3, except that 30.3 g (0.42 mol) of AA, 35.0 g (0.42 mol) of 48% by mass sodium hydroxide aqueous solution, 4.8 g (0.09 mol) of AN, 10.5 g (0.09 mol) of 2-HEA, 0.32 g of potassium persulfate, 0.093 g (0.0006 mol) of MBAA, and 221.9 g of deionized water were used.
[0096] [Example 6] In a 1 L reaction vessel equipped with a stirrer, thermometer, N2 gas inlet tube, reflux condenser, and dropping funnel, 288.9 g of deionized water was charged, and N2 gas was blown in to deoxygenate the system. Then, 15.1 g (0.21 mol) of AA, 17.5 g (0.21 mol) of 48% by mass sodium hydroxide aqueous solution, 0.81 g (0.003 mol) of AE-200, 10.1 g (0.09 mol) of 2-HEA, 0.46 g (0.003 mol) of MBAA, and 0.81 g of potassium persulfate were charged, and the internal temperature was raised to 70°C and maintained for 5 hours. After that, the internal temperature was cooled to below 40°C to obtain an aqueous solution containing the copolymer.
[0097] [Example 7] An aqueous solution containing the copolymer was obtained in the same manner as in Example 1, except that 32.4 g (0.45 mol) of AA, 37.5 g (0.45 mol) of a 48% by mass sodium hydroxide aqueous solution, 4.8 g (0.09 mol) of AN, 7.0 g (0.06 mol) of 2-HEA, 0.32 g of potassium persulfate, and 221.9 g of deionized water were used.
[0098] [Comparative Example 1] A monomer aqueous solution was prepared by adding 33.5 g (0.46 mol) of AA, 38.7 g (0.46 mol) of 48% sodium hydroxide aqueous solution, 1.9 g (0.02 mol) of HAAm, 1.9 g (0.02 mol) of 2-HEA, 0.27 g of potassium persulfate, and 50 g of deionized water to a resealable vial with an internal volume of 500 mL and mixing the contents. Separately from the above, 179.6 g of deionized water was charged into a 1 L reaction vessel equipped with a stirrer, thermometer, N2 gas inlet tube, reflux condenser, and dropping funnel. After deoxygenating the system by blowing in N2 gas, the internal temperature was raised to 70°C. Subsequently, the prepared monomer aqueous solution was added to the reaction vessel dropwise over 3 hours using a dropping funnel while stirring. After the addition, the internal temperature was maintained at 70°C for 2 hours. After that, the internal temperature was cooled to below 40°C to obtain an aqueous solution containing the copolymer.
[0099] [Comparative Example 2] An aqueous solution containing the copolymer was obtained in the same manner as in Example 1, except that 29.7 g (0.41 mol) of AA, 34.3 g (0.41 mol) of 48% by mass sodium hydroxide aqueous solution, 4.0 g (0.08 mol) of AN, 1.8 g (0.01 mol) of 2-MEA instead of 2-HEA, 0.27 g of potassium persulfate, and 176.9 g of deionized water were used.
[0100] [Comparative Example 3] An aqueous solution containing the copolymer was obtained in the same manner as in Example 3, except that 28.8 g (0.40 mol) of AA, 33.3 g (0.40 mol) of 48% by mass sodium hydroxide aqueous solution, 17.0 g (0.32 mol) of AN, 9.3 g (0.08 mol) of 2-HEA, 0.37 g (0.0024 mol) of MBAA, 0.43 g of potassium persulfate, and 302.6 g of deionized water were used.
[0101] [Comparative Example 4] An aqueous solution containing the copolymer was obtained in the same manner as in Example 2, except that 287.9 g of deionized water, 16.9 g (0.23 mol) of AA, 19.5 g (0.23 mol) of 48% by mass sodium hydroxide aqueous solution, 16.2 g (0.31 mol) of AN, 7.0 g (0.06 mol) of 2-HEA, 0.13 g (0.0006 mol) of DEGDA instead of MBAA, and 0.32 g of potassium persulfate were used.
[0102] <Rating> The copolymers obtained in the above examples / comparative examples were used to measure the following properties. The test method is as follows.
[0103] [Initial expansion rate] The initial expansion rate was determined by following the procedure below. [Electrode fabrication] As the electrode active material, 23.3 parts by mass of artificial graphite (Jiangxi Zichen Technology, G-49), 5.8 parts by mass of silicon monoxide (Shin-Etsu Chemical Co., Ltd., KSC-1265), and 0.9 parts by mass of a copolymer aqueous solution (based on solid content) were kneaded together. Furthermore, water was added and kneaded until the solid content concentration reached 58% by mass to prepare a negative electrode slurry. The obtained negative electrode slurry was applied to a rolled copper foil with a thickness of 18 μm, dried, and then the rolled copper foil and the coating were tightly bonded using a roll press (Ohno Roll Co., Ltd.). Next, a heat treatment (reduced pressure, 100°C, 12 hours or more) was performed to produce the negative electrode. The thickness of the active material layer in the obtained negative electrode was 36 μm, and the capacity density of the negative electrode was 3.5 mAh / cm³. 2 That was the case.
[0104] [Assembly of coin cells] A coin cell (CR2032) was fabricated, comprising the negative electrode prepared as described above, the positive electrode, separator, and electrolyte described below. • Positive electrode: Li (manufactured by Honjo Metal Co., Ltd.) • Separator: Glass filter (Manufactured by Advantech Co., Ltd., product name GA-100) • Electrolyte: A solution prepared by dissolving LiPF6 at a concentration of 1 mol / L in a solvent obtained by mixing ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, and adding 1% by mass of vinylene carbonate (VC) and 1% by mass of fluoroethylene carbonate (FEC), which are electrolyte additives.
[0105] [Measurement of initial expansion rate] Each coin cell prepared as described above was charged to 0.005V at 30°C with a current equivalent to 0.2C. The secondary battery was then disassembled in a drying booth, and the negative electrode was removed. After washing with dimethyl carbonate and drying under reduced pressure at 23°C for 1 hour, the electrode thickness was measured using a micrometer. The active material layer thickness was calculated by subtracting the copper foil thickness from the electrode thickness, and the expansion rate (initial expansion rate) was calculated using the following formula. Expansion rate (initial expansion rate) = (thickness of active material layer after disassembly) / (thickness of active material layer during battery fabrication) × 100 [%]
[0106] [Capacity retention rate after 100 cycles] The capacity retention rate after 100 cycles was determined by following the procedure below. [Electrode fabrication] As the electrode active material, 23.3 parts by mass of artificial graphite (Jiangxi Zichen Technology, G-49), 5.8 parts by mass of silicon monoxide (Shin-Etsu Chemical Co., Ltd., KSC-1265), and 0.9 parts by mass of a copolymer aqueous solution (based on solid content) were kneaded together. Furthermore, water was added and kneaded until the solid content concentration reached 58% by mass to prepare a negative electrode slurry. The obtained negative electrode slurry was applied to a rolled copper foil with a thickness of 18 μm, dried, and then the rolled copper foil and the coating were tightly bonded using a roll press (Ohno Roll Co., Ltd.). Next, a heat treatment (reduced pressure, 100°C, 12 hours or more) was performed to produce the negative electrode. The thickness of the active material layer in the obtained negative electrode was 36 μm, and the capacity density of the negative electrode was 3.5 mAh / cm³. 2 That was the case.
[0107] [Assembly of coin cells] A coin cell (CR2032) was fabricated, comprising the negative electrode created above, the positive electrode described below, a separator, and an electrolyte. ·Positive electrode: LiNi 0.5 Co 0.2 Mn 0.3 O2 (manufactured by Hachiyama Co., Ltd.) • Separator: Glass filter (Manufactured by Advantech Co., Ltd., product name GA-100) • Electrolyte: A solution prepared by dissolving LiPF6 at a concentration of 1 mol / L in a solvent obtained by mixing ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, and adding 1% by mass of vinylene carbonate (VC) and 1% by mass of fluoroethylene carbonate (FEC), which are electrolyte additives.
[0108] [Measurement of discharge capacity after 100 cycles] For each coin cell prepared as described above, the battery was aged by performing the following operation three times at 30°C: charging to 4.2V with a current equivalent to 0.1C, discharging to 2.5V with a current equivalent to 0.1C, charging to 4.2V with a current equivalent to 0.5C, and discharging to 2.5V with a current equivalent to 0.5C. Next, the battery was charged to 4.2V with a current equivalent to 0.5C, discharged to SOC50 with a current equivalent to 0.5C, discharged at a constant current of 0.2C for 12 seconds, charged for 24 seconds with a current equivalent to 0.1C, discharged at a constant current of 0.5C for 12 seconds, charged for 1 minute with a current equivalent to 0.1C, discharged at a constant current of 1C for 12 seconds, charged for 2 minutes with a current equivalent to 0.1C, discharged at a constant current of 2C for 12 seconds, and then discharged to 2.5V with a current equivalent to 0.2C. The initial discharge capacity was then measured. Next, the battery was charged to 4.2V with a current equivalent to 1C, and then discharged to 2.5V with a current equivalent to 1C for 97 cycles (cycles 4-100). Subsequently, the same procedure as when measuring the initial discharge capacity was performed, and the discharge capacity after 100 cycles was measured.
[0109] The test results are summarized in the table below. In the table below, the values for each component represent the amount (in moles) of each component per 100 moles of all monomer components used in the preparation of the copolymer. TIFF2026166615000003.tif73159 [Industrial applicability]
[0110] This disclosure is suitably used as a power source for mobile communication devices, portable electronic devices, electric bicycles, electric motorcycles, electric vehicles, and the like. According to one aspect of this disclosure, the expansion of electrodes during the initial stages of charging and discharging of secondary batteries is suppressed, and such secondary batteries can contribute to solving environmental problems from the perspective of reducing waste by extending battery life, and thus have great industrial potential.
Claims
1. A secondary battery binder containing a copolymer comprising repeating units represented by the following formula (I) and repeating units containing acidic functional groups, In the copolymer, the amount of the acidic functional group-containing repeating unit is 65 mol% or more. A secondary battery binder in which the amount of the acidic functional group-containing repeating unit per mole of the repeating unit represented by formula (I) is 30 moles or less in the copolymer. 【Chemistry 1】 [In the formula, R 1 [where m is a hydrogen atom or a methyl group; m is an integer from 2 to 5 independently; and n is an integer from 1 to 50 independently in each occurrence.]
2. The secondary battery binder according to claim 1, wherein the copolymer further comprises nitrile group-containing repeating units.
3. The secondary battery binder according to claim 1 or 2, wherein the amount of the acidic functional group-containing repeating unit per mole of the repeating unit represented by formula (I) is 5 to 30 moles in the copolymer.
4. The secondary battery binder according to claim 2, wherein the amount of the nitrile group-containing repeating units in the copolymer is 5 to 20 mol%.
5. The secondary battery binder according to claim 1 or 2, wherein the amount of repeating units represented by formula (I) in the copolymer is 3 mol% or less.
6. A slurry for secondary batteries, A slurry comprising the secondary battery binder according to claim 1 or 2, and water.
7. The slurry according to claim 6, further comprising an electrode active material.
8. A method for manufacturing a secondary battery, comprising the step of coating with the slurry described in claim 6.
9. A secondary battery binder according to claim 1 or 2, or an electrode containing a component derived from the secondary battery binder.
10. An electrode comprising a dried slurry according to claim 6.
11. A secondary battery comprising the electrode described in claim 9.
Citation Information
Patent Citations
Nonaqueous electrolyte secondary battery and manufacturing method thereof
JP2012049061A
Silicon electrode binder
JP2020533771A